A Waqf Empowerment Model Based on Benefit Analysis - Supriatna, Encup; Syarif, Dede; Afrilia, Astri; Sundari, Asri; Setia, Paelani (Journal of Islamic Thought and Civilization, 2024)
Waqf endowment is an act of worship with various socioeconomic implications. At the time of the Prophet Muhammad (SAW), waqf functioned as an instrument to meet the financial needs of the community. Indonesia has the highest Muslim population in the world. Hence, it has a high potential for creating waqf endowments. This study aims to analyze the usefulness of waqf and develop a model to empower waqf endowments, especially in West Java. A quantitative approach was used for data collection by distributing questionnaires to the beneficiaries of waqf. Moreover, in-depth interviews and literature studies were also conducted to collect the data. The results showed that the respondents perceived the religious dimension of waqf as very useful, although they found its economic dimension of little use and significance. Moreover, empowerment models regarding the economic dimension are presented in this research for some of the most important waqf endowments in West Java in particular and in Indonesia in general, namely mosques and educational institutions (schools/madrasas).